Molecular conformations of DNA targets captured by model nanoarrays. Issue 36 (6th September 2017) - Hao, X.; Josephs, E. A.; Gu, Q.; Ye, T.
Abstract : We generated nanoarrays with tailored surface functionalities and morphologies to probe how single DNA molecules interact with surface heterogeneities. Abstract : An open question in single molecule nanoarrays is how the chemical and morphological heterogeneities of the solid support affect the properties of biomacromolecules. We generated arrays that allowed individually-resolvable DNA molecules to interact with tailored surface heterogeneities and revealed how molecular conformations are impacted by surface interactions.